Outphasing mobile communications transmitter - Mendes, João Paulo Louro (2018)
This dissertation proposes the implementation of an Outphasing PA architecture for mobile communication transmitters. In this work, the main focus is the development of a functional prototype that demonstrates power efficiency improvements at high power back-off, when compared to traditional configurations. The proposed architecture suggests the signal component separator to be implemented in the digital domain, allow the device to become more flexible. Also, unlike the traditional Outphasing, the input power at the branches is not constant: it can change freely to benefit PAE at higher OPBO. The amplifier was implemented using two 10 W GaN HEMT and it obtained a maximum power between 43.42 dBm and 43.73 dBm in bandwidth of [2.25;2.40] GHz (its operational bandwidth). The drain efficiency, the maximum values vary between 64.3 % and 58.4 %, and the maximum PAE between 55.9 % and 58.4 %. For 2.30 GHz, its best operational frequency, PAE is higher than 50 % until -6.0 dB of OPBO. To be able to implement this configuration on a mobile communication system in a less demanding manner for the digital processing unit, the usage of polynomial equations, that describe the power of the input signal into the necessary branch signals, has been studied in this document. In the performed tests, it was observed that the power and the efficiency performances of the PA does not substantially change, even with the usage of low order polynomials. Yet, low order polynomials may compromise the linearity of the amplifier. When tested with a LTE signal with PAPR of 10.33 dB or with a 4-carrier GSM signal with PAPR of 6.2 dB, both with a bandwidth of 10 MHz, the amplifier shows considerable amounts of distortion. That is demonstrated in the three evaluated performance metrics: AM-AM; AM-PM; and ACLR. The average efficiency levels reach 50 % for the GSM signal and 36 % for the LTE one. After digital predistortion was applied, an improvement of the evaluated metric was observed. This scenario was tested for the LTE signal, using the 7th order polynomial in the signal component separator. The ACLR lowered from -21 dBc to -56 dBc; the AM-AM variation from 2.3 dB to 0.6 dB; and the AM-PM variation from 61.0o to 3.2o. This while the average efficiency increased from 30 % to 36 %. In the end, the objectives of this work were concluded, and the produced prototype can equate to some of the state-of-the-art reference works.